2017
DOI: 10.1038/s41598-017-09710-3
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cell-derived extracellular vesicles mediate the acute phase response and sickness behaviour associated with CNS inflammation

Abstract: Brain injury elicits a systemic acute-phase response (APR), which is responsible for co-ordinating the peripheral immunological response to injury. To date, the mechanisms responsible for signalling the presence of injury or disease to selectively activate responses in distant organs were unclear. Circulating endogenous extracellular vesicles (EVs) are increased after brain injury and have the potential to carry targeted injury signals around the body. Here, we examined the potential of EVs, isolated from rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…In fact, Kurachi et al showed that EVs derived from various ECs (aortic, brain, umbilical) have similar effects on oligodendrocytes [ 63 ], which suggests potential similarities among EVs from different vascular beds in executing some actions. Although cross-talk between the vascular lineages has not been examined, it has been demonstrated by adoptive transfer of BMEC-derived EVs (in vivo) that these vesicles can have an effect on other organ systems such as the liver [ 64 , 65 ].…”
Section: Ec-derived Evs: Role In Cns Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Kurachi et al showed that EVs derived from various ECs (aortic, brain, umbilical) have similar effects on oligodendrocytes [ 63 ], which suggests potential similarities among EVs from different vascular beds in executing some actions. Although cross-talk between the vascular lineages has not been examined, it has been demonstrated by adoptive transfer of BMEC-derived EVs (in vivo) that these vesicles can have an effect on other organ systems such as the liver [ 64 , 65 ].…”
Section: Ec-derived Evs: Role In Cns Pathologymentioning
confidence: 99%
“…Further highlighting the correlation with inflammatory state, plasma levels of CD31 + EMPs were significantly reduced in MS patients treated with IFN-β1a, a standard therapy for RRMS, and declined in the same direction as clinical disability [ 88 ]. Such inflammatory responses are not limited to MS, as intracerebral injection of IL1-β into rats was also found to prompt release of endothelial cell-derived EVs, which became sequestered in the liver and mediated the acute-phase response and sickness behavior associated with CNS inflammation [ 64 ]. While it is important to keep in mind that the circulating and liver-bound EVs described in these studies were not explicitly identified as coming from the CNS microvasculature, when EVs released from IL1-β-treated BMEC cultures where injected back into rats, they elicited the same behavioral pathology.…”
Section: Ec-derived Evs: Role In Cns Pathologymentioning
confidence: 99%
“…The response was seen at all ages examined, but there was an age-specific difference in the magnitude of this response. Our own experiments have shown that IL-1β injected into the brain parenchyma does not leave the brain ( Couch et al, 2017 ) and the effect of the combination of the 1 ng intracerebral dose with a 100 ng intravenous dose compared to the 100 ng intravenous alone suggests that simple leakage from the brain is not a factor here. Indeed, the presence of 1 ng IL-1β in the brain seems to inhibit the APR in these young animals and the local production of IL-1β and ICAM-1 was unaffected by high circulating concentrations of IL-1β.…”
Section: Discussionmentioning
confidence: 84%
“…(Stoelting Co., Illinois, U.S.) was used to automatically measure the distance travelled, time spent in centre, and immobility time. The number of rearing events, including both unsupported and supported against the walls of the enclosure, were counted manually as an indication of exploratory behaviour [40][41][42] .…”
Section: Animals and Treatmentsmentioning
confidence: 99%